Children's Skills in The Storybook “Bibo Can't Sleep” - Wahyuningsih (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Children are an important period of age development, this period is often called the golden age. At the age of children, skills need to be developed and trained continuously so that they can develop as desired. This skill is the ability of a human being to complete a given task and complete it smoothly and quickly. The research method used is qualitative research with a type of document study research. Because this research uses document studies, researchers understand the contents of the story. This book tells the story of a child who cannot sleep due to the many mosquitoes that disturb his third ear. The results of this study found three skills contained in the story